Fish community dynamics in a cold temperate tidal lagoon in the Wadden Sea, in relation to changes in environmental conditions ... - Odongo Otieno, Victor (Universität Bremen, 2024)
The thesis investigated the effects of long-term and seasonal changes in environmental conditions on fish communities in the Wadden Sea. Using a monthly fish monitoring dataset from 2007 to 2019, a total of 55 fish species were recorded, including 8 new observations of Lusitanian, boreal, and Atlantic species, while four species from earlier surveys (1989-1995) were no longer present. The fish community was dominated by 22 species, which accounted for over 95% of the total abundance. These species exhibited three distinct trends: dome-shaped, increasing, or decreasing, influenced by winter temperatures which impacted recruitment. The analysis revealed seasonal groupings based on species’ temperature preferences, affecting their migration patterns. Warming autumn temperatures delayed cod (Gadus morhua) immigration and whiting (Merlangius merlangus) emigration into the Wadden Sea. Environmental factors, primarily water temperature, salinity, and chlorophyll a, explained 18% of fish community variation on a ...